2006
DOI: 10.1101/gad.1441306
|View full text |Cite
|
Sign up to set email alerts
|

Txr1: a transcriptional regulator of thrombospondin-1 that modulates cellular sensitivity to taxanes

Abstract: Using transcripts initiated at a chromosomally integrated retrovirus-based promoter to perturb gene expression randomly in human prostate cancer cells, we isolated cell clones resistant to taxane lethality and discovered the role of a previously uncharacterized gene, txr1, in this phenotype. We show that txr1 impedes taxane-induced apoptosis in tumor cells by transcriptionally down-regulating the production of thrombospondin-1 (TSP-1)-known earlier for both its anti-angiogenic and proapoptotic actions. Decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 48 publications
5
58
0
1
Order By: Relevance
“…A recently reported in vitro study proposed another mechanism of resistance to taxanes (14). Using function-based screens, the investigators identified a previously unknown gene, TXR1 (15), whose protein overexpression conferred resistance to paclitaxel.…”
mentioning
confidence: 99%
“…A recently reported in vitro study proposed another mechanism of resistance to taxanes (14). Using function-based screens, the investigators identified a previously unknown gene, TXR1 (15), whose protein overexpression conferred resistance to paclitaxel.…”
mentioning
confidence: 99%
“…Inactivations of TXR1 by CD47, or activation of TSP1, were also shown to enhance taxolinduced cytotoxicity in tumor cells. In combination, results by these authors suggested that TXR1, as a thrombin-mediated regulator, was a potential therapeutic target (12). However, the correlation between TXR1 and drug resistance in breast cancer remained to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen et al (12) identified the taxol resistance gene 1 (TXR1) and showed that it reduced the secretion of the apoptosis-inducing protein, thrombospondin-1 (TSP1). TSP1 has been shown to induce apoptosis and inhibit angiogenesis (13), roles that are consistent with a taxol-resistant phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…TSP-1/CD47 interaction can also differentially affect cancer cell sensitivity toward chemotherapeutics. For instance, TSP-1 sensitized taxol-resistant prostate cancer cells to taxol treatment (Lih et al, 2006), whereas a blocking anti-CD47 antibody decreases cytotoxicity of taxol treatment. Of note, taxol resistance is partly regulated by the txr1 gene, a gene known to downregulate TSP-1 expression.…”
Section: Direct Anti-cancer Effects Via Cross Linking Of Tumor Expresmentioning
confidence: 99%
“…Of note, taxol resistance is partly regulated by the txr1 gene, a gene known to downregulate TSP-1 expression. Correspondingly, treatment with a TSP-1 mimetic peptide sensitized cells to taxol by activating CD47 signaling (Lih et al, 2006). In contrast, treatment of thyroid carcinoma cells with a CD47-binding peptide reduced doxorubicin and camtothecin cytotoxicity (Rath et al, 2006).…”
Section: Direct Anti-cancer Effects Via Cross Linking Of Tumor Expresmentioning
confidence: 99%